Structural Functionalism Analysis On Children Labourers Phenomena In Jember Regency (International Journal of Scientific Research and Management (IJSRM), 2017)
The phenomenon of child labourer is a social fact that is difficult to eliminate in society (social system) because it is still functional for social structures such as family, business, and child labourer itself. Various policies and regulations have been made by the government, but the implementation has not been effective in dealing with child labourer issues. The aims of this study is to describe: (1) What is the reason parents do not ask their children to school, even though they are not burdened with the cost of education; (2) What is the reason of the child involve into the world of work; And (3) What is the basic consideration of employers employing children, despite being prohibited by the Manpower Act Number 13 Year 2003 and the Law of the Republic of Indonesia number 1 Year 2000. Based on the theory of structural functionalism, it explained that society is a social system consisting of parts or elements that are interrelated; united in order and balance. Changes that occur in one part cause changes to other parts. The basic assumption is that any structure in the social system is functional and can also be dis-functional to other social structures when the structure has negative consequences. The certain consequences, both functional and dysfunctional have a particular purpose and are recognized by the system element so that it is manifest (manifest function). Other unrecognized elements are latency or having latency function. Through the perspective of the structural functionalism theory, it can be explained that the phenomenon of child labourer is closely related to the functioning and dysfunction of social structures such as family, business, and child labourer itself, and in the process of interaction between structures within a particular social system of purpose. It is a manifest or latency to the balance of the social system, so the phenomenon of child labourer persists and persists in society. This research was conducted in Jember regency, precisely in 3 (three) sub districts, namely Sumbersari, Kaliwates, and Patrang. The location is based on the consideration that there is an almost equal spread of labourers in the region because each region has the same potential for child labourers for various reasons and considerations